Cardiovascular imaging in the diagnosis and monitoring of cardiotoxicity: cardiovascular magnetic resonance and nuclear cardiology. (May 2016) - Pepe, Alessia; Pizzino, Fausto; Gargiulo, Paola; Perrone-Filardi, Pasquale; Cadeddu, Christian; Mele, Donato; Monte, Ines; Novo, Giuseppina; Zito, Concetta; Di Bella, Gianluca
Abstract : Chemotherapy-induced cardiotoxicity (CTX) is a determining factor for the quality of life and mortality of patients administered potentially cardiotoxic drugs and in long-term cancer survivors. Therefore, prevention and early detection of CTX are highly desirable, as is the exploration of alternative therapeutic strategies and/or the proposal of potentially cardioprotective treatments. In recent years, cardiovascular imaging has acquired a pivotal role in this setting. Although echocardiography remains the diagnostic method most used to monitor cancer patients, the need for more reliable, reproducible and accurate detection of early chemotherapy-induced CTX has encouraged the introduction of second-line advanced imaging modalities, such as cardiac magnetic resonance (CMR) and nuclear techniques, into the clinical setting. This review of the Working Group on Drug Cardiotoxicity and Cardioprotection of the Italian Society of Cardiology aims to afford an overview of the most important findings from the literature about the role of CMR and nuclear techniques in the management of chemotherapy-treated patients, describe conventional and new parameters for detecting CTX from both diagnostic and prognostic perspectives and provide integrated insight into the role of CMR and nuclear techniques compared with other imaging tools and versus the positions of the most important international societies.